(3GdeaUd aj GdfMhs - (3GdnqRnerNnTpQj GdNhGQRej, CHh GdbGSe, LGQ Gddg, eMehO Hf YeQ Hf eMeO Hf CMeO, (B538 (3g`s ((3YHO Gddg Hf NejSs)
(3ChdgG (B:s
(3bGd GdCSJGP GdEeGe(B...(3GdReNTQj(B...(3Gddg CMeO Ydi Cf LYdfj ef YdeGA GdYQHjI hLHdfj Ydi GdZVH ddYQH hGdYUHjI(B...s
(3BNQgG (B:s
(3hEPG cGfhG eef jMPahf eY EecGf GdEOZGe aj jJSY hjQJbj agh eY YOe GdMPa(B. (3Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B7(3,U(B178s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B822s
(3cTa GdXfhf(B:(3L(B2(3,U(B1774s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdfMhs